Unraveling the malate biosynthesis during development of Torreya grandis nuts - Yan Jingwei; Chen Weijie; Zeng Hao; Cheng Hao; Suo Jinwei; Yu Chenliang; Yang Baoru; Lou Heqiang; Song Lili; Wu Jiasheng (Elsevier BV, 2025)
Torreya grandis is a characteristic rare economic tree species in subtropical mountainous areas. The kernels of T. grandis have rich content of organic acids, and malate is the predominant organic acid in T. grandis kernels. However, the contents, biosynthesis/metabolism pathway and transcriptional regulation of malate in developing T. grandis kernels remain completely unknown. Here, the organic acid composition in developing T. grandis kernels was first analyzed. The results showed that the content of malate was increased during the maturation T. grandis kernels. A malate synthase (TgMLS) gene might be involved in the accumulation of malate based on transcriptome data, gene expression and enzyme activity analysis. Transient expression of TgMLS in tobacco resulted in the high malate synthase activity and malate content. Furthermore, a basic helix-loop-helix transcription factor (bHLH), TgbHLH87 was identified to positively regulate the TgMLS expression via directly binding the TgMLS promoter. Our finding contributes to mechanism underlying malate accumulation in T. grandis kernels.